2019
DOI: 10.3389/fimmu.2019.01691
|View full text |Cite
|
Sign up to set email alerts
|

An IL-4/21 Inverted Cytokine Receptor Improving CAR-T Cell Potency in Immunosuppressive Solid-Tumor Microenvironment

Abstract: Incorporation of inverted cytokine receptor (ICR) such as interleukin (IL)-4 vs. IL-7 (4/7) ICR is one strategy to improve the antitumor activities of chimeric antigen receptor (CAR) modified T (CAR-T) cells facing immunosuppressive cytokines. Here we report a novel interleukin (IL)-4 vs. IL-21 ICR (4/21 ICR) that enhanced CAR-T cell potency in IL-4 + tumor milieu via a different working-mechanism from 4/7 ICR. Upon IL-4 stimulation, 4/21 ICR activated the STAT3 pathway and promoted Th17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 30 publications
0
64
0
1
Order By: Relevance
“…For instance, our recent study demonstrated that IL12 armored GPC3redirected CAR T cells could greatly improve the antitumor activities in mouse model even with large tumor burdens (41). We also showed that introducing an IL4/21 inverted cytokine receptor into the CAR-GPC3 construct improved the CAR T-cell potency in vitro and in vivo (37). In another recent study, our group disrupted PD-1 gene expression in CAR-GPC3 T cells using the CRISPR/Cas9 gene-editing system.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For instance, our recent study demonstrated that IL12 armored GPC3redirected CAR T cells could greatly improve the antitumor activities in mouse model even with large tumor burdens (41). We also showed that introducing an IL4/21 inverted cytokine receptor into the CAR-GPC3 construct improved the CAR T-cell potency in vitro and in vivo (37). In another recent study, our group disrupted PD-1 gene expression in CAR-GPC3 T cells using the CRISPR/Cas9 gene-editing system.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, anti-GPC3 mAbs had good safety profiles in previous studies (34,35), although significant clinical benefit has yet to be established in phase II clinical trials. Recently, we demonstrated that GPC3targeted CAR T cells could eliminate GPC3 þ HCC cells in vitro and eradicate GPC3 þ HCC tumor xenografts in mice (36)(37)(38). Therefore, in the present prospective phase I studies, we explored the safety and potential efficacy of CAR-GPC3 T-cell therapy in adult Chinese patients with advanced GPC3 þ HCC.…”
Section: Introductionmentioning
confidence: 96%
“…In line with this, a novel anti-CD19 CAR-T cells with constitutive activation of STAT3 showed increased proliferation and reduced terminal differentiation of CAR-T cells, and conferred superior anti-tumor effects [ 174 ]. Similarly, CAR-T cells expressing the ectodomain of the IL-4 receptor and the end domain of the IL-21 receptor activated the STAT3 pathway and enhanced Th17-like polarization, representing a potential clinical CAR-T therapy for solid tumors enriching IL-4 [ 175 ]. These studies suggest a beneficial effect of STAT3 activation in CAR-T cells.…”
Section: Integrating Stat3 In Combination Cancer Immunotherapymentioning
confidence: 99%
“…They showed that, upon binding of IL-4, 4/21 ICR not only activates the STAT3 pathway and polarizes engineered T cells into Th17-like cells but also promotes antitumor cytotoxicity in vitro. Moreover, 4/21 ICR CAR T cells could persist and eradicate IL-4-expressing tumors in vivo (47).…”
Section: Manipulating Car T Cells To Express Cytokines and Their Recementioning
confidence: 99%